PENGARUH PENDEKATAN PEMBELAJARAN TERHADAP KEMAMPUAN PENALARAN DAN KOMUNIKASI MATEMATIKA SISWA SMP NEGERI KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Asria Ratau (MATEMATIKA DAN PEMBELAJARAN, 2016)
The study is a quasi–eksperimental research which aims at examining (1) students’ activities and responses on the learning process by using open-ended problem approach, (2) students’ activities and responses on the learning process by using problem-solving approach, (3) the infleunce of open-ended problem approach and problem-solving approach on mathematical reasoning and communicating skills of students at SMP Negeri in Leihitu subdistrict of Central Maluku district. The population of the study was class VIII students in 6 public junior high schools (SMPN) with acreditation B in Leihitu subdistrict of Central Maluku district. Samples were selected by employing simple random sampling with schools serial number; then, from the choses school, it was determined the experimental class 1 and experimental class 2 taught by using open-ended problem approach and problem-solving approach. The collecting data consisted of students’ study result, students’ learning activities data, and students responses’ data on the learning instruments. The results of the study show that the students’ activities using open-ended problem approach is in good category and students responses’ is in fairly positiv category. Then, the students’ activities using problem-solving approach is in good category and students’ responses is in fairly positive category. The result of the inferensial analysis using multivariate analysis of variance test (MANOVA) shows that the learning approach (open ended problem and problem solving) gives significant impact on mathematical reasoning and commucating skills of class VIII students at SMP Negeri in Leihitu subdistrict of Central Maluku District. Key Words : Learning Approach, Skills Reasoning, Communication Skills